The transition to open innovation: a case study in the banking industry - Fasnacht, Daniel Peter (2005)
The business model of many banks -selling financial products, services and advising customers -has not changed significantly during the last twenty-five years. Nevertheless, the process by which ideas are identified, required knowledge is incorporated and utilised, innovations developed and distributed, has changed radically. The reasons for this transformation are the volatile, uncertain geopolitical climate driven by increasing competition, economic pressure, regulatory changes, technological innovations, and the changing nature of demand. Although banking has traditionally been a conservative industry, resistant to change, these strategic challenges are forcing firms to make extensive adaptations to the changing environment, with innovation as a source of competitive advantage. The blend of openness, flexibility, discipline, and focus on the core business captures the innovation zeitgeist. The overall phenomenon that will drive change, beneath the surface of banking in years to come, is anticipated to be the shift from a closed to an open innovation paradigm. In recent years, most banks have embraced “open architecture” as a model that offers clients a full range of products, regardless of suppliers. Some banks have gone even further and restructured their client advisory processes as a complementary service to their product portfolio, with the aim of increasing customer value. Managing multiple product offerings, serving, and advising clients across the globe triggered investments in organisational and technological infrastructures. The capability for open, flexible, and aligned interactions is required for all business practices, but is particularly important for integrating acquired institutions. This capacity is crucial for the bank’s growth strategy of onshore banking operations for wealthy private clients. The bank, whose experience forms the basis of this doctorate, has been a leading example in the financial service industry of a firm that has embraced the need for open innovation. It realised that the strategic value of the future will be the combination of technology, knowledge, and innovation, as given emphasis to some extent in the knowledge-based view of the firm. This study examines how open innovation was adopted and developed in the context of the banking industry. In particular, it analyses how the studied bank responded to the trends and negotiated the transition to open innovation. This transition was based upon organisational and technological innovation and required a set of new management practices focused upon developing dynamic capabilities. The findings, represented in a proposed integrative framework, provide multiple contributions to knowledge. The core of the theoretical contribution builds on the concept of leveraging capabilities as a set of resources and capabilities aligned through social capital and based on an open innovation culture. This overall picture and novel account, shows that firms can manage strategic change and simultaneously increase efficiency and flexibility by aligning various initiatives and strategies. Another key contribution of this management research is its applied nature, obtained by seeking information that explains the process, rather than just the outcomes of social actions. Through this process, it became apparent that the successful transition relies heavily on the firm’s leadership and their ability to provide the organisation with conditions that facilitate innovation and learning. These key issues addressed the integrative aspects of the study, in which theory-and practice-led research combined contributed to the production of knowledge for both academics and managers.